Pengaruh Lingkungan Kerja Dan Motivasi Terhadap Kinerja Pegawai Pada Dinas Komunikasi, Informatika Dan Statistik Provinsi Bengkulu - Desi Maryani; Tito Irwanto; Yanto Effendi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study was to determine the effect of work environment and motivation on employee performance at the Bengkulu Province Communication, Information and Statistics Agency. The sample in this study was 87 ASN at the Bengkulu Province Communication, Information and Statistics Office. The data was collected using a questionnaire and the analytical methods used were multiple linear regression, determination test and hypothesis testing. The results showed that the regression value Y = 12.775 + 0.319X1 + 0.394X2 + 3.848, with a positive regression direction, the work environment had a significant effect on employee performance at the Communication, Information and Statistics Office of Bengkulu Province, because the significant value was 0.000, which was smaller than 0, 05. This means that the work environment at the Bengkulu Province Communication, Information and Statistics Office is increasing. Motivation has a significant effect on employee performance at the Bengkulu Province Communication, Information and Statistics Office, because the significant value of 0.000 is smaller than 0.05. This means that the increased motivation will improve the performance of the Bengkulu Province Communication, Information and Statistics Office. Work environment and motivation have a significant effect on employee performance at the Bengkulu Province Communication, Information and Statistics Office because the significant value of 0.000 is smaller than 0.05, thus the initial hypothesis proposed is proven (Ha is accepted). That is, there is a significant influence between the work environment and motivation on performance together. The coefficient of determination of R square is 0.410. This means that the work environment and motivation affect performance by 41% while the rest (100-41% = 59%) is influenced by other causal factors not examined in this study.